Plant Silicon Amendment Does Not Reduce Population Growth of Schizaphis graminum or Host Quality for the Parasitoid Lysiphlebus testaceipes - Sampaio, M. V.; Franco, G. M.; Lima, D. T.; Oliveira, A. R.C.; Silva, P. F.; Santos, A. L.Z. [UNESP]; Resende, A. V.M.; Santos, F. A.A.; Girão, L. V.C. (Springer Nature, 2020)
Interactions between different pest control methods can affect Integrated Pest Management efficiency. This study sought to evaluate (1) if Si accumulation is related to the level of constitutive resistance in sorghum genotypes, (2) the level of Si induces resistance by antibiosis in sorghum genotypes with different levels of constitutive resistance to Schizaphis graminum (Rondani) (reared individualized or in colonies), and (3) the fitness of Lysiphlebus testaceipes (Cresson) in aphids reared on Si-treated and untreated plants. Several experiments were conducted under greenhouse conditions, using sorghum genotypes with different levels of resistance grown in pots with or without the addition of Si to the soil. The susceptible (BR007B), moderately resistant (GB3B), and highly resistant (TX430XGR111) genotypes all absorbed more Si when it was added to the soil compared with when it was not amended. However, the final Si content of treated plants was not related to the level of constitutive resistance among treated genotypes. While Si soil application did reduce the fecundity of individualized aphids reared on the susceptible and moderately resistant sorghum plants, it did not reduce populational growth of aphid colonies, independent of the level of plant’s constitutive resistance. Parasitoid (L. testaceipes) had higher weight when reared from aphids fed on plants with added Si. Sorghum × constitutive resistance × S. graminum interactions were affected by plant Si content only for individualized aphids but not for aphid colonies. Sorghum × S. graminum × L. testaceipes interactions suggest that Si can have, overall, a positive effect on the biological control of S. graminum.
Keywords: Antibiosis; Fitness; Induced resistance; Parasitoid; Plant resistant; Sorghum bicolor